Teknik Behavior dalam Menangani Perilaku Indisipliner Siswa pada Korban Perceraian di SMP Diponegoro Sleman Yogyakarta - Slamet wahyudi, Muchamad Agus (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
This study examined behavioral approach in dealing with studentsâ indiscipline behavior at SMP Diponegoro Depok Sleman Yogyakarta whose family background of divorce. Qualitative descriptive methodwas applied to reveal the above phenomenon and the data were collected by observation and in-depth interview. It revealed that there were three main steps in applying this behavior approach. Firstly, assessment was essentially conducted in advance to investigate the underlying factors which cause indiscipline to happen. The second step was a goal setting; discussing with students about the consequences that might be faced when they engage in undisciplined behavior. At this stage, the researcher along with the students had succeeded in devising a plan to solve the problem. The last stage was that carrying out the research to assess students followed by counseling contract, relaxation, modeling, reward and punishment, encouragement, time-out, home assignment and ending with the evaluation phase. The results found that behavioral technique was one of effective approaches in guidance and counseling to handle maladaptive on adaptive behavior, and this approach was very appropriate to handle undisciplined students in school. Â Ø¯Ø±Ø³ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¹ÙÙÙØ§ Ø¹Ù Ø§ÙÙØ¯Ø®Ù Ø§ÙØ³ÙÙÙÙ ÙÙ ÙØ¹Ø§ÙØ¬Ø© Ø¸Ø§ÙØ±Ø© "Ø§ÙÙØ§ Ø§ÙØ¶Ø¨Ø§Ø·"Â  ÙØ¯Ù Ø·ÙØ§Ø¨ Ø§ÙÙØ¯Ø±Ø³Ø© Ø§ÙÙØªÙØ³Ø·Ø© Ø§ÙØ¹Ø§ÙØ© Ø¯ÙÙÙÙÙØºÙØ±Ù Ø¯ÙÙÙÙ Ø³ÙÙÙÙØ§Ù ÙÙØºÙØ§ÙØ±ØªØ§ Ø¨Ø®ÙÙÙØ© ÙØ±Ø§Ù Ø§ÙÙØ§ÙØ¯ÙÙ.Â  ÙÙÙØ´Ù ÙØ°Ù Ø§ÙØ¸Ø§ÙØ±Ø©Ø Ø§Ø³ØªØ®Ø¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙÙØ¬ Ø§ÙØ¨ØØ« Ø§ÙÙØµÙÙ Ø§ÙÙÙÙÙ. ÙØ¬ÙÙØ¹Øª Ø§ÙØ¨ÙØ§ÙØ§Øª Ø¹Ù Ø·Ø±ÙÙ Ø§ÙÙÙØ§ØØ¸Ø© ÙØ§ÙÙÙØ§Ø¨ÙØ© Ø§ÙØ´Ø®ØµÙØ©. ÙØØµÙ Ø§ÙØ¨Ø§ØØ« Ø¹ÙÙ ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ«Ø ÙÙÙ Ø«ÙØ© Ø«ÙØ§Ø« Ø®Ø·ÙØ§Øª Ø±Ø¦ÙØ³ÙØ© ÙÙ ØªØ·Ø¨ÙÙ Ø§ÙÙØ¯Ø®Ù Ø§ÙØ³ÙÙÙÙØ ÙÙÙ Ø£ÙÙØ§ : Ø§ÙØªÙÙÙÙØ ÙÙÙ Ø¹ÙÙÙØ© Ø£ÙÙÙØ© ÙÙÙØ´Ù Ø¹Ù Ø®ÙÙÙØ© Ø³ÙÙÙ "Ø§ÙÙØ§ Ø§ÙØ¶Ø¨Ø§Ø·"Â  Â Ø Ø«Ø§ÙÙØ§ : Ø¥Ø«Ø¨Ø§Øª Ø§ÙØ£ÙØ¯Ø§ÙØ ÙÙÙ Ø§ÙÙÙØ§ÙØ´Ø© ÙØ¹ Ø§ÙØ·ÙØ§Ø¨ Ø¹ÙÂ  Ø§ÙÙÙØ¬ÙÙØ© Ø§ÙØ°Ù ÙÙØ§Ø¬ÙÙØ§ Ø§ÙØ·ÙØ§Ø¨ Ø¥Ø°Ø§ ÙØ§Ø±Ø³ÙØ§ Ø³ÙÙÙ "Ø§ÙÙØ§ Ø§ÙØ¶Ø¨Ø§Ø·"Â  . ÙÙ ÙØ°Ù Ø§ÙÙØ±ØÙØ© Ø§Ø³ØªØ·Ø§Ø¹ Ø§ÙØ¨Ø§ØØ« ÙØ¹ Ø§ÙØ·ÙØ§Ø¨ ÙØ¶Ø¹ Ø®Ø·Ø© ÙØÙ Ø§ÙÙØ´Ø§ÙÙ.Â  Ø«Ø§ÙØ«Ø§ :Â  Ø¥Ù ØªØ·Ø¨ÙÙ ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ø§ÙØ¨Ø¯Ø§ÙØ©Ø ÙÙ Ø¥Ø¬Ø±Ø§Ø¡ Ø§ÙØªÙÙÙÙ ØªØ¬Ø§Ù Ø§ÙØ·ÙØ§Ø¨ Ø«Ù Ø¹ÙØ¯ Ø§ÙÙØ´ÙØ±Ø©Ø ÙØ§ÙØ§Ø³ØªØ±Ø®Ø§Ø¡Ø ÙØ§ÙØªØµÙÙÙØ Ø§ÙØªÙØ±ÙÙ ÙØ§ÙØ¹ÙØ§Ø¨Ø ÙØ§ÙØªÙÙÙØ©Ø ÙÙÙØ° Ø§ÙÙÙØªØ ÙØ§ÙÙØ§Ø¬Ø¨ Ø§ÙÙÙØ²ÙÙØ ÙÙÙ Ø§ÙØ£Ø®ÙØ± Ø§ÙØªÙÙÙÙ. Ø¨ÙØ°Ø§ ÙÙÙÙ Ø§ÙØ£Ø³ÙÙØ¨ Ø§ÙØ³ÙÙÙÙ Ø£ØØ¯ Ø§ÙÙØ¯Ø§Ø®Ù ÙÙ Ø§ÙØªÙØ¹ÙØ© ÙØ§ÙØ¥Ø±Ø´Ø§Ø¯ ÙÙØ¹Ø§ÙØ¬Ø© Ø¹Ø¯Ù ÙØ¯Ø±Ø© Ø§ÙØ·Ø§ÙØ¨ Ø¹ÙÙ Ø§ÙØªÙÙÙÙØ ÙÙØ°Ø§ Ø§ÙØ£Ø³ÙÙØ¨ ÙØ§Ø¬Ø¹ ÙÙÙØ§Ø³Ø¨ ÙØ¹ÙØ§Ø¬ Ø³ÙÙÙ Ø§ÙÙØ§Ø§ÙØ¶Ø¨Ø§Ø· Ø§ÙÙØ§ÙØ¹ Ø¹ÙØ¯ Ø§ÙØ·ÙØ§Ø¨ ÙÙ Ø§ÙÙØ¯Ø±Ø³Ø©.